2020
DOI: 10.1007/s00424-020-02401-5
|View full text |Cite
|
Sign up to set email alerts
|

Improved adaptation to physical stress in mice overexpressing SUR2A is associated with changes in the pattern of Q-T interval

Abstract: The purpose of this study was to determine whether increased expression of SUR2A, a regulatory subunit of sarcolemmal ATP-sensitive K + (K ATP) channels, improves adaptation to physical stress and regulates cardiac electrophysiology in physical stress. All experiments have been done on transgenic mice in which SUR2A expression was controlled by cytomegalovirus immediate-early (CMV) promoter (SUR2A) and their littermate wild-type controls (WT). The levels of mRNA in heart tissue were measured by real-time RT-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Nevertheless, at least for the circadian data it might be possible that analysis of light and dark phases separately for QT-RR relationships may over-control for endogenous changes in rate and repolarization mediated by circadian fluctuations in rhythm and autonomic modulation. Sudhir et al ( Sudhir et al, 2020 ) recently explored adaptation of QT to physical stress in mice overexpressing SUR2A, a regulatory subunit of sarcolemmal ATP-sensitive K + (K ATP ) channels. Although the results show highly complex pattern of changes over time in both transgenic and control mice, only corrected QT intervals (using Mitchell’s formula) are presented in the study, limiting ability to evaluate the effects of exercise on the native QT interval.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, at least for the circadian data it might be possible that analysis of light and dark phases separately for QT-RR relationships may over-control for endogenous changes in rate and repolarization mediated by circadian fluctuations in rhythm and autonomic modulation. Sudhir et al ( Sudhir et al, 2020 ) recently explored adaptation of QT to physical stress in mice overexpressing SUR2A, a regulatory subunit of sarcolemmal ATP-sensitive K + (K ATP ) channels. Although the results show highly complex pattern of changes over time in both transgenic and control mice, only corrected QT intervals (using Mitchell’s formula) are presented in the study, limiting ability to evaluate the effects of exercise on the native QT interval.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, at least for the circadian data it might be possible that analysis of light and dark phases separately for QT-RR relationships may over-control for endogenous changes in rate and repolarization mediated by circadian fluctuations in rhythm and autonomic modulation. Sudhir et al (Sudhir et al, 2020) (Kmecova and Klimas, 2010) for rats and by Mitchell et al (1998) for mice, resulted in marked difference between the measured QT interval and the QTc interval for a wide range of atrial pacing rates in both species (Figure 1). At the present, it is hard to conclude what is the optimal way of QT correction in rodent and if correction is required at all.…”
Section: Figurementioning
confidence: 99%
“…Increased SUR2A protein expression was reported to exert an important biological impact on cardiac function as selective upregulation of the subunit in the heart provided improved tolerance and endurance to stress by increasing the density of sarcolemmal K ATP channels and presumably activity. 30 To confirm that increased SUR2A protein expression in response to PDBu proceeded via the mTORC1 complex, NNVMs were pre-treated with rapamycin. The macrolide attenuated PDBu-mediated hypertrophy, suppressed basal mTOR phosphorylation, and inhibited the increased phosphorylation of the threonine 389 residue of p70S6K.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, coincident with p70S6K recruitment and the concomitant hypertrophic response, PDBu treatment led to the upregulation of the K ATP channel subunit SUR2A whereas no change in Kir6.2 protein levels was observed. Increased SUR2A protein expression was reported to exert an important biological impact on cardiac function as selective upregulation of the subunit in the heart provided improved tolerance and endurance to stress by increasing the density of sarcolemmal K ATP channels and presumably activity 30 . To confirm that increased SUR2A protein expression in response to PDBu proceeded via the mTORC1 complex, NNVMs were pre‐treated with rapamycin.…”
Section: Discussionmentioning
confidence: 99%
“…Early evidence indicated that sarcolemma ATP-sensitive potassium (sarcK ATP ) channels play a crucial role in ischemic preconditioning and myocardial resistance to ischemia, which close during general conditions and open in response to increased [ADP]/[ATP], linking membrane excitability to the balance of ATP production and shortening action potential (AP) duration (APD) via the efflux of K + ( Garrott et al, 2017 ; Sudhir et al, 2020 ). SarcK ATP channels improve adaptation to physical stress and profoundly alter membrane excitability and other membrane potential-related functions, such as Ca 2+ overload, thus helping to maintain cellular homeostasis during cardiac challenge (i.v.…”
Section: K Atp Channels In Cardiovascular Diseasesmentioning
confidence: 99%